Not all Roads are Created Equal: A Framework for the Allocation of Welfare-Increasing Transport Infrastructure - Ramos, Barbara. (2017)
Abstract: This dissertation provides a framework to guide the selection of domestic transport infrastructure projects by providing a metric to assess their general equilibrium effects. The framework is comprised of three components: (i) a decision criterion that directs the selection of transport infrastructure projects, (ii) a model that delivers the necessary information for the application of the decision criterion, and (iii) a factor return analysis that identifies distributional consequences. Once developed, the framework is applied to three selected transport infrastructure construction/rehabilitation projects: two that have already been completed, constituting ex post applications, and one that is still under implementation, exemplifying an ex ante application of the framework.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Economics and International Business.; Advisor: Carsten Kowalczyk.; Committee: Steven Block, and Bernard Hoekman.; Keywords: Economics, and Transportation.